Kontribusi Perusahaan melalui Program Corporate Social Responsibility dalam Penanganan Masalah Stunting di Kalimantan (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
The problem of stunting is a health issue that is not only handled by the government but also companies through their Corporate Social Responsibility activities. The purpose of this study is to see what kind of contribution and impact of CSR programs organized by companies to overcome the problem of stunting in Kalimantan. This study is a literature research. The source of data in this research is obtained from secondary sources, namely company annual reports, books and scientific journals relevant to this research. The data analysis technique in this research was an interactive model consisting of data condensation, data presentation and conclusion drawing. The results of this study indicate that the contribution of three companies, namely PT Pertamina Patra Niaga (PN) Regional Kalimantan, PT Adaro Indonesia, and PT Pertamina Eksplorasi dan Produksi (EP) Asset 5 Sangasanga Field focus on increasing the capacity and quality of health cadres through providing education, training and stunting detection tools as well as providing additional food for pregnant women and toddlers. Through the contribution of these companies, there is a positive impact, an improvement in the health status of stunted toddlers and a decrease in the prevalence of stunting in each area intervened by the company. The results of this study also show the achievement of SDGs on points 2 and 3 as a result of the contributions made by companies through their CSR programs in handling stunting problems. Keywords: Company, Corporate Social Responsibility, Health, Stunting.